Identification of key genes related to intramuscular fat deposition in Beijing-You chicken by mRNA and miRNA transcriptome analysis - Kai Gai; Yu Ge; Dapeng Liu; He Zhang; Bailin Cong; Shihao Guo; Yizheng Liu; Kai Xing; Xiaolong Qi; Xiangguo Wang; Longfei Xiao; Cheng Long; et al. (Poultry Science, 2023)
ABSTRACT: Intramuscular fat (IMF) is an important factor affecting chicken quality. However, the age-related mechanism of IMF deposition has not yet been elucidated. In this study, the IMF, phospholipids (PL), triglycerides (TG), and fatty acid (FA) content in the breast muscle of Beijing-You chicken (BJY) at 1, 56, 98, and 120 d of age was measured, and mRNA and miRNA sequencing was integrated to explore the regulatory genes of IMF deposition. The results showed that the IMF content of BJY at 1 d of age was significantly higher than that at later stage of birth (P < 0.05). The transcriptome sequencing results showed that 7, 225 differentially expressed genes (DEGs) and 243 differentially expressed miRNAs (DE-miRNAs) were identified. The cluster analysis showed that the expression of DEGs and DE-miRNAs at 1 d of age was significantly different from that at later stages of birth. Furthermore, a potential mRNA-miRNA regulatory network related to IMF deposition was established by weighted gene co-expression network analysis (WGCNA); gga-miR-29c-3p-PIK3R1, gga-miR-6701-3p-PTEN, gga-miR-363-3p-PTEN, gga-miR-1563-WWP1, gga-miR-449c/d-5p-TRAF6, and gga-miR-6701-3p-BMPR1B were identified as key mRNA-miRNA pairs for the regulation of IMF deposition. These results will help elucidate the mechanism of IMF formation mediated by miRNAs in chickens, and provide a theoretical foundation for the genetic improvement of broiler meat quality.